Pengaruh Good Corporate Governance dan Leverage Terhadap Manajemen Laba - Fanani, Yayuk; Sulistyo, Sulistyo; Mustikowati, Rita Indah (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2018)
This study aims to determine the effect of good corporate governance and leverage on earnings management. The population used is manufacturing companies listed on the Indonesia Stock Exchange in 2014-2015 and the sample determination method used is purposive judgment sampling. Samples obtained were 44 companies. Data analysis techniques used are descriptive analysis, classic assumption test, multiple linear regression test, and hypothesis testing. This study found that simultaneous good corporate governance and corporate leverage influence earnings management. Partially, this research found that good corporate governance is proxied by institutional ownership (KI), managerial ownership (KM), audit committee (KA), company size (UK), and leverage affect earnings management, while the independent board of commissioners (DKI) and the board of directors (DD) have no effect on earnings management.